2015
DOI: 10.1002/cncr.29433
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of an Australian supportive care needs assessment tool for Indigenous patients with cancer

Abstract: BACKGROUND: There are significant disparities in cancer outcomes between Indigenous and non-Indigenous Australians. Identifying the unmet supportive care needs of Indigenous Australians with cancer is imperative to improve their cancer care. The purpose of the current study was to test the psychometric properties of a supportive cancer care needs assessment tool for Indigenous people (SCNAT-IP) with cancer. METHODS: The SCNAT-IP was administered to 248 Indigenous Australians diagnosed with a range of cancer ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 28 publications
0
67
0
1
Order By: Relevance
“…Incomplete or delayed access to information by GP has been linked to preventable medical errors. Compared to a previous study which recruited 248 indigenous cancer patients from hospitals in Queensland, 49 18,19,49 the higher proportion of medical charts at PHC services with missing cancer stage is of concern and it may be attributed to poor communication between hospitals and PHC services. 18,19 Patients with comorbidities may be more likely to develop long-term relationships with their PHC services or GP.…”
Section: Communication About Cancer In Primary Carementioning
confidence: 75%
“…Incomplete or delayed access to information by GP has been linked to preventable medical errors. Compared to a previous study which recruited 248 indigenous cancer patients from hospitals in Queensland, 49 18,19,49 the higher proportion of medical charts at PHC services with missing cancer stage is of concern and it may be attributed to poor communication between hospitals and PHC services. 18,19 Patients with comorbidities may be more likely to develop long-term relationships with their PHC services or GP.…”
Section: Communication About Cancer In Primary Carementioning
confidence: 75%
“…This manuscript combines data collected from two cross-sectional studies carried out in Queensland, Australia that assessed the unmet needs of people with cancer: the Indigenous Supportive Care Needs Study (referred to here as "Indigenous study") (Garvey et al, 2015) and the Care and Wellbeing Study (referred to here as the "Non-Indigenous study"). The two studies were conducted by the same research team using similar recruitment and data collection procedures.…”
Section: Participantsmentioning
confidence: 99%
“…However, no study has directly compared the unmet needs between Indigenous and Non-Indigenous Australians (Harrison et al, 2009). Previous research on the unmet needs of Queensland, Australian Indigenous people with cancer and demonstrated that money worries (29%) and needs related to physical and psychological domains (11%) were the most frequently reported (Garvey et al, 2015). While Australian studies of cancer cohorts (Indigenous and Non-Indigenous combined) have reported that fear about their cancer spreading (40%) was most frequently reported (Sanson-Fisher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Participants were assessed through a face-to-face interview for their needs using a Supportive Care Needs Assessment Tool for Indigenous People (SCNAT-IP) (Garvey et al, 2015); distress using the Distress Thermometer (DT) (Roth et al, 1998); and on worry using the Worry Chart (CWC) (Gramling, Anthony, Frierson, & Bowen, 2007). Inclusion criteria included being ≥18 years, identified as Aboriginal and/ or Torres Strait Islander, had a cancer diagnosis, and attended the Princess Alexandra Hospital for their care.…”
Section: Assessment Tool and Moderate To High Unmet Needs Identificmentioning
confidence: 99%
“…Responses were then grouped as: "no need, satisfied with help received, or needed a little more help" vs. "needed some or a lot more help" (referred to here as "high needs") (Garvey et al, 2015). Distress was measured according to the National Comprehensive Cancer Network Guidelines on distress management (National Comprehensive Cancer Network, 2015), where patients scoring four (≥4) or higher on the DT were considered distressed and in need to be referred to an appropriate supportive service.…”
Section: Assessment Tool and Moderate To High Unmet Needs Identificmentioning
confidence: 99%